Germination pattern of three Mangifera species - Wahab, Zakaria; Tengku Maamun, Tengku Ab. Malik; Muhamad, Masri (Malaysian Agricultural Research and Development Institute (MARDI), 2002)
The germination patterns of three Mangifera species at the seedbed stage were described. Seeds of M. foetida (Bacang), M. odorata (Kuini) and clones of M. indica (Telur, Tangkai Panjang and Sala) were sown vertically with the dorsal edge in the sandy seedbed. Germination and seedling emergence appear to be regulated physically by the fibrous endocarp. The endocarp resistance to seedling emergence consequently resulted in seedling abnormalities, especially in strongly polyembryonic cultivar such as Sala. Seed position during sowing, to a certain extent, may reduce the percentage of occurrence of seedling abnormalities. Seedling height, leaf number and the number of days for the first leaf flush to become green were related to the number of seedlings produced per seed and were cultivar-specific.